EKSPERIMENTASI PEMBELAJARAN MATEMATIKA DENGAN MENGGUNAKAN MODEL PEMBELAJARAN SAVI DAN RECIPROCAL TEACHING PADA MATERI OPERASI HITUNG BENTUK ALJABAR DITINJAU DARI GAYA BELAJAR SISWA SMP NEGERI DI KABUPATEN SLEMAN - Muanifah, Mahmudah Titi; Budiyono, Budiyono; Subanti, Sri (Jurnal Pembelajaran Matematika, 2014)
The objective of research was to find out: (1) which students had the better mathematics learning achievement, those treated with SAVI, those with Reciprocal teaching or those with direct learning model in the topics of algebraic arithmetic operation l, (2) which students had the better mathematics learning achievement, those with visual, those with auditory or those with kinesthetic learning style, (3) in each learning model, which students had the better mathematics learning achievement, those with visual, those with auditory or those with kinesthetic learning style, and (4) in each learning style, which students had the better mathematics learning achievement, those treated with SAVI, those with Reciprocal teaching or those with direct learning model in the topics of algebraic arithmetic operation.This study was a quasi experimental research with a 3 Ã 3 factorial design. The population of research was all of the VII graders of Junior High Schools in Sleman Regency. The sample was taken using stratified cluster random sampling technique. The sample consisted of 285 students: 96 for the experiment 1 class, 94 for the experiment 2 class, and 95 for the control class. Considering the hypothesis testing, the following conclusions could be drawn. (1) The learning achievement of the students treated with SAVI learning model, Reciprocal Teaching learning model and direct learning model was equally good. (2) The learning achievement of the students with visual learning style was better than that of those with kinesthetic one. But, that of those with visual learning style was as good as that of those with auditory one, and that of those with auditory was as good as that of those with kinesthetic one. (3) In SAVI, reciprocal teaching, and direct learning models, the learning achievement of the students with visual, auditory and kinesthetic learning styles was equally good. (4) In the categories of visual, auditory and kinesthetic learning style, the learning achievement of the students treated with SAVI, reciprocal teaching and direct learning was equally good.Â Keywords: Somatic, Auditory, Visual and Intellectual (SAVI), Reciprocal Teaching (RT), Student Learning Style.